IMPROVING THE STUDENTS’ WRITING SKILL THROUGH LOOPING STRATEGY TO THE SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 15 OF PALEMBANG - Noviati Noviati (HOLISTICS, 2020)
One of strategy that can use to increase students’ achievement in writing report paragraph is looping strategy. Looping can help you focus your thought on a subject, find the core or center of your thought, and pinpoint a main idea on which to elaborate. It means that looping strategy can help students exploring their thinking through writing. The appropriate strategies will be able to give the significant effects toward students’ writing achievement. Based the reason above, the topic of this researchis, “improving the students’ writing skill through looping strategy to the seventh grade students of junior high school 15 of Palembang”. The result of independent test was the post test in each group was 5. 86 and significance level was 0.000 since 0.000 is lower than 0.05 it means that there is significant difference in writing in those two groups. It concluded that the students in experimental group made better achievement than those in control group. This indicates that in improving the students’ writing skill through looping strategy to the seventh grade students of junior high school 15 of Palembang it can be say effective in improving writing skill and it could help them to write procedure paragraphs easier than before.